Prevention of gestational diabetes mellitus - N. V. Artymuk; O. N. Novikova; O. V. Glazovskaya (Фундаментальная и клиническая медицина)
Gestational diabetes mellitus (GSD) is defined as hyperglycemia of variable degree with onset or first recognition during pregnancy which does not meet the criteria of clinical diabetes mellitus (DM). The growing incidence of GSD is a global health problem, affecting from 9% to 12% of pregnancies worldwide. In this review, we focused on the key aspects of GSD prevention. Major risk factors of GSD development include family history, past medical history of GSD, fetal macrosomia in previous pregnancies, and obesity. At primary treatment, lifestyle interventions (e.g., change of the dietary pattern) may represent an efficient measure, and here we consider several types of diets and dietary supplements (e.g., myoinositol, folic acid, and probiotics) that might be useful to mitigate GSD. Physical activity and specialised psychological care during pregnancy planning, during the pregnancy and in the postpartum period has a number of positive effects. Adequate perception of GSD, which might be improved by psychotherapy, directly correlates with adherence to therapeutic and preventive measures. The complex of dietary interventions, increased physical activity, and psychological care can significantly reduce the risk of adverse pregnancy outcomes.